Hypothermic ante situm resection in tumors of the hepatocaval confluence - Mehrabi, Arianeb; Fonouni, Hamidreza; Golriz, Mohammad; Hofer, Stefan; Hafezi, Mohammadreza; Rahbari, Nuh Nabi; Weitz, Jürgen; Büchler, Markus W.; Schmidt, Jan (Digestive surgery, 2011)
Primary liver malignancies together with metastatic liver tumors are among the most common tumors in human. The best available treatment option for these diseases is surgical resection. One major parameter which had been considered as contraindication for liver resection owing to technical difficulties in achieving tumor-free margins was the involvement of the hepatocaval confluence. To overcome this problem, several techniques including hypothermic in situ, ante situm and ex situ liver resection have been introduced. The common basis for these liver resections is the total vascular exclusion of the liver, and perfusion of the organ by preservation solution under hypothermic conditions. The major indications for the ante situm liver resection are tumors in the liver that are either unresectable or inadequately resectable by conventional surgery because they involve the venous confluence and/or the retrohepatic vena cava, or are in close proximity to them. This technique is a realistic option to achieve surgical cure or substantial gain of life time with quality of life in otherwise unresectable tumors of the liver. Due to fewer anastomoses, the ante situm approach is easier and safer than the ex situ approach, with an acceptable morbidity and mortality rate. Patient selection is of utmost importance to achieve a good outcome. To minimize the postoperative morbidities and mortality, this procedure requires a multidisciplinary approach and should be performed in experienced centers with a high case volume of hepatobiliary surgeries.